Structural and vibrational properties of α- and π-SnS polymorphs for photovoltaic applications. (15th January 2020) - Guc, Maxim; Andrade-Arvizu, Jacob; Ahmet, Ibbi Y.; Oliva, Florian; Placidi, Marcel; Alcobé, Xavier; Saucedo, Edgardo; Pérez-Rodríguez, Alejandro; Johnson, Andrew L.; Izquierdo-Roca, Victor
Abstract: Tin sulphide (SnS) has attracted the attention of the photovoltaic (PV) community due to the combination of desirable optical properties, and its binary and earth abundant elemental composition, which should lead to relatively simple synthesis. However, currently the best SnS based PV device efficiency remains at 4.36%. Limited performance of this material is attributed to band gap alignment issues, deviations in doping concentration and poor film morphology. In this context Raman spectroscopy (RS) analysis can be useful as it facilitates the accurate evaluation of material properties. In this study we present a RS study, supported by X-ray diffraction and wavelength dispersive X-ray measurements, of α- and π-SnS thin films. In particular a complete description of SnS vibrational properties is made using six excitation wavelengths, including excitation energies coupled with certain optical band to band transitions, which leads to close to resonance measurement conditions. This study describes an in-depth analysis of the Raman spectra of both SnS structural polymorphs, including the differences in the number of observed peaks, with their relative intensities and Raman shift. Additionally, we evaluate the impact of low temperature heat treatment on SnS. These results explicitly present how the variation of the [S]/[Sn] ratio in samples deposited by different methods can lead to significant and correlated shifts in the relative positions of Raman peaks, which is only observed in the α-SnS phase. Furthermore, we discuss the suitability of using Raman spectroscopy based methodologies to extract fine stoichiometric variations in different α-SnS samples. Graphical abstract: Image, graphical abstract